THE ROLES OF PARENTS IN YOUNG LEARNERS’ ENGLISH VOCABULARY MASTERY AT SD NEGERI BANDUNGAN 01 - Wulan Septiyana Dewi; Budiati (Universitas Ngudi Waluyo, 2025)
Character is an important element in fictional work besides the other elements. In fiction, character reveals a textual representation of human being, or occasionally another creature. Character is the player in the story and it makes the story alive. Every character in a story has characterization. Characterization is the process of conveying information about characters in fiction. In other words, characterization is the way an author describes their characters’ characteristic in the story. The importance of parents' role in children's language development has been shown to have a significant impact, particularly in English language learning. The method used was descriptive qualitative with total sampling, involving 55 parents as respondents. Data were collected through questionnaires, observation, interviews and documentation. The results showed that parental involvement has a positive impact on children's English learning. The role of parents in parenting was recorded as excellent with a percentage of (58.2%), communication was excellent (50.9%), willingness to volunteer was very good (61.8%), home learning was very good (69.1%), decision making was very good (49.1%), and collaboration with the community was very good (52.7%). The active role of parents has a significant effect on children's English vocabulary acquisition and creates a pleasant learning atmosphere that supports optimal language development.